PWE-097 How long do freka percutaneous endoscopic gastrostomy (peg) tubes last? a long-term retrospective analysis. (17th June 2017) - Troth, T; Siau, K; Dhanda, A; Gibson, E; Robinson, L; Fisher, N
Abstract : Introduction: PEG (percutaneous endoscopic gastrostomy) tubes are used for long term enteral feeding in patients who are unable to meet their nutritional requirements orally. There is little published data on the longevity of PEG tubes. We aimed to assess this within our adult nutrition service, where we use Freka tubes preferentially and only plan replacement if tube complications arise. Method: PEGs are inserted using a conventional pull-through technique; 15Fr Freka PEG tubes are the tube of choice. We used our endoscopy database to identify all patients who underwent PEG insertion from 2010 to 2013 inclusive, and analysed follow-up details from a clinical database until January 2017. We recorded PEG-related indications, complications, re-interventions, and patient and PEG-tube survival. Time-to-event analysis was performed using Kaplan-Meier estimates, with Cox regression to assess predictors of PEG tube failure. Results: 277 patients underwent PEG insertion over 4 years. Median age was 73 (IQR 59–82.) Indication for insertion was available for 255; the commonest indications were cerebrovascular disease, 93 (36%), neurodegenerative disease, 72 (28%) and oropharyngeal cancer, 51 (20%). Among the total cohort of 277 patients, a total of 46 (17%) underwent PEG exchange. Indications for exchange were: split or broken tube, 17 (6.1%), peristomal sepsis 7 (2.5%), buried bumper 19 (6.9%), dislodged 3 (1.1%). The median interval to tube replacement for any reason was 924 days (IQR 593–1135.) Among indications for PEG tube, oropharyngeal cancer was predictive of greater PEG-tube longevity (hazard ratio for replacement 0.281, p=0.039) Seven (2.5%) patients had elective tube removal when no longer required and 5 (1.8%) had tube extensions inserted for post-pyloric feeding. Median follow up to death, tube exchange or removal or study census point was 1072 days (IQR 152–1, 554). Thirty-day mortality in the whole cohort was 10.6% Conclusion: In this cohort with extended follow up of > 3 years, a relatively low proportion of patients (18%) required tube exchange after a median of > 2.5 years. This observation may be useful for patient information and may form the basis for future comparative studies Disclosure of Interest: None Declared